Acoustic Measurements Through the Life Span: Jitter, Shimmer, and Standard Deviation of Fundamental Frequency - Spazzapan, Evelyn Alves [UNESP]; Fabbron, Eliana Maria Gradim [UNESP]; Toledo, Willians Walace Fante [UNESP]; Paula, Alana de Souza [UNESP]; Marino, Viviane Cristina de Castro [UNESP] (Elsevier, 2024)
Objective: To verify changes in acoustic parameters, namely jitter, shimmer, and standard deviation of the fundamental frequency (dp fo), through the life span of vocally healthy Brazilian Portuguese speakers. Method: In total, 526 voice recordings of subjects without complaints and without vocal disorders, aged between 5 and 93 years old, were included. The recordings were divided into 12 age groups (5 to 7, 8 to 9, 10 to 11, 12, 13 to 15, 16 to 18, 19 to 29, 30 to 39, 40 to 49, 50 to 59, 60 to 69, and 70 to 93 years old). Acoustic analysis was carried out, based on the sustained emission of the vowel /a/, extracting the parameters jitter, shimmer, and dp fo, using the Multi-Dimensional Voice Program software. The two-way ANOVAtest was used to investigate possible differences between age groups, followed by the Sidak Post-Hoc test. Results: Related to jitter, children present higher values compared with the elderly. In adults and the elderly, the jitter measurement does not reflect the changes resulting from aging in both sexes. Women have a higher jitter value compared with men. As for the shimmer, this measurement is high in the child population with stability during adulthood and, in the elderly, it was observed that the shimmer was sensitive to indicate vocal changes in the male population. In general, there are no sex differences on this measurement. Finally, for dp fo, the study found higher values in the child population, with a reduction with aging until stabilizing in adults and the elderly. Higher values were observed for females compared with males. Conclusion: Jitter, shimmer, and dp fo changed through the life span, being elevated for the child population, remaining stable in the adult population, and with smaller changes during aging.
Keywords: Voice—Acoustics—Child—Adult—Aged—Aging